PERBANDINGAN CITRA LANDSAT DENGAN BPS UNTUK PREDIKSI PRODUKSI PADI SAWAH (STUDI KASUS: KABUPATEN BLITAR, KABUPATEN LUMAJANG, KABUPATEN MALANG) - Kurniawan, Rizky Fariz Andry; Ermatita, . (Fakultas Ilmu Komputer UPN Veteran Jakarta, 2020)
The current population of Indonesia has affected the existing land in each district. This leads to an imbalance in land use. One example is paddy field. The impact of the problem produced by rice fields is rice. According to the Central Statistic Agency (BPS), most rice production in Indonesia is located in East Java province. This research was conducted in Blitar Regency, Malang Regency, Lumajang Regency from 2015 to 2017. This research uses the Normalized Difference Vegetation Index (NDVI) method. Classification using Maximum Likelihood. Obtained Overall Accuracy value of 73.53% and Kappa 27.45%.